AN ANALYSIS OF SLANG WORDS USED IN ‘SUICIDE SQUAD’ MOVIE - Ninda Setia Tanti; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: This research aimed to find out the types of slang words that used by all characters in „Suicide Squad‟ movie. The design of the research was descriptive qualitative research. The data source was the „Suicide Squad‟ movie directed by David Ayer. The movie was released in 2016 and its duration was about 2 hours 17 minutes. The data of this research were the slang words that were found in „Suicide Squad‟ movie. The data were collected by watching, observing, and writing down the slang words found in the movie. To analyze the slang words, this study was applied Allan and Burridge‟s (2006) theory. The results of the analysis showed that 103 data of slang words were found in the „Suicide Squad‟ movie, with Flippant as the most dominant type of slang words that used in „Suicide Squad‟ movie. In conclusion, slang is a common word that used in spoken language for daily life. We need to understand the slang words in order not to get misunderstanding.Key Words: Language, Slang, Movie